My Dead Women Won't Let Me Forget: the Body as a Discursive Device of Memory in the Poetry of Nidia Marina González Vásquez - Arroyo Carvajal, Yordan (2025)
This article presents, in the first part, approaches, proposals, problems and challenges about the poetic work of the Costa Rican writer Nidia Marina González Vásquez. In the second part, as theoretical support, some approaches are provided regarding issues related to memory, time, memories and oblivion, with the support of Saramago (1994 / 2010), Ricoeur (2000), Boethius (ed. 2015), and Arroyo Carvajal (2023b). In the third part, reference is made to issues linked to the body-text-textile from Weil (1940-1941), Moosekian (2015), Retamal Zapata (2017), Sanz (2023), and Rodríguez Gutiérrez and Araújo Nieto (2025); subsequently, a philological and literary analysis of the meanings of the body as a discursive device of memory in the poetry book Anamnesis (2022a) is presented. As part of the results, it was possible to observe an ascending thread from the interpretation of the meaning of the title of the book, its two epigraphs (Alexia Ugalde Quesada and Cristina Peri Rossi) and some of the poems studied here, which allowed us to confirm our hypothesis regarding the ethical and aesthetic use of the body as a discursive device of memory.